دراسات توازنات الأطوار في الجملة الثنائية لميتافانادات الصوديوم مع موليبدات الكالسيوم NaVO3-CaMoO4 (Latakia University Journal -Basic Sciences Series, 2017)
تم في هذا البحث دراسةتوازنات الأطوار في الجملة الثنائية (NaVO3-CaMoO4)مخبريا (في مخابر كلية العلوم)حيث يعتبر مفهوم التحولات الطورية , الأساس للعديد من العلوم الطبيعية , كالكيمياء والفيزياء وعلم الأحياء ,ومنها يعد المنطلق للعلوم الهندسية كالهندسة الميكانيكية والكهربائية وهندسة المواد . تعتبر التحولات الطورية شائعة في الطبيعة , فقد استفاد منها الإنسان في تطوير وتحسين مواد قديمة , ومنها استطاع التبحر في التحولات الطورية غير المألوفة (الموائع الفائقة, الناقلية الفائقة, المعادن الزجاجية) والتي يمكن من خلالها ان يحل العديد من المشاكل التقنية التي كانت تواجه التكنولوجيا ,ومازال هذا الباب مفتوحا مادامت إرادة تحسين الحياة على أساس التقدم العلمي موجودة. وعند دراسة تحولات أي مادة ضمن أطوارها ,يدرس بما يسمى بمخطط التوازن او مخطط الأطوار , كون توازن المادة موافق للطاقة الأصغرية عند تغيير المتحولات التيرموديناميكية . عمليا من المستحيل الوصول لحالة التوازن , وتكمن أهمية البحث في الحصول على مركبات بلورية في الجمل الثنائية لميتا فانادات الصوديوم مع موليبدات الكالسيوم لما لهذه الأملاح من خواص نوعية في مجالات التكنولوجيا لذا كان من المهم دراسة إمكانية الحصول على أطوار جديدة عند نسب مولية مختلفة ورسم مخططات توازنات الأطوار لها . لاسيما أن الأملاح المأخوذة للدراسة تملك بنى بلورية مختلفة وبالتالي يمكن التنبؤ بأن نواتج الدراسة ستكون هامة وجيدة.وتبين هذه الدراسة تشكل محلول صلب على اساس موليبدات الكالسيوم حيث تنحل ميتافانادات الصوديوم في موليبدات الكالسيوم حتى 40%من ميتافانادات الصوديوم.In this research study Toisat phase in bilateral Wholesale (NaVO3-CaMoO4) in vitro (in the laboratories of the Faculty of Science), where is the concept of phase transitions, the basis for many of the natural sciences chemistry , physics and biology, which is the premise of science engineering, mechanical and electrical such as engineering and materials engineering. Transitions are considered the metaphase common in nature, it has benefited rights in the development and improvement of old materials, which was able to elaborate the phase transitions unfamiliar (Fluid high, conductivity high, glass metals) and in which they can solve many of the technical problems that were facing the technology, and this is still the door open as long as the will to improve life on the basis of scientific progress exist.??When examining any material changes within the stages, studying the so-called scheme of balance or eccentric scheme, since the material balance energy Minimal when changing variables Altermdinamekih. Practically impossible to reach a state of equilibrium, lies the importance of research to obtain crystalline compounds in the binary strings of dead sodium vanadate with calcium molybdate what these salts from the properties of the quality in the areas of technology, so it was important to study the possibility of obtaining new phases at different Molar ratios and fee balances schemes her eccentric. Especially since the salts derived for the study have different crystalline structures and can therefore predict that the outputs of the study will be important and good.This study shows form the core of a solution on the basis of calcium molybdate where dissolved sodium molybdateMataffanadat in calcium up to 40% of sodium Mataffanadat.